Ayahuasca partially preserves striatal integrity in juvenile non-human primates exposed to chronic stress: evidence from stereological evaluation - Lira-Bandeira, Wigínio Gabriel; Mendonça Batista, Lílian Andrade Carlos; Medeiros-Bandeira, Andréa Silva; Góis Morais, Paulo Leonardo Araújo; Pereira, Luiz Roberto Fernandes; Meiroz-Grilo, Maria Lara Porpino; Cavalcante, Jeferson Souza; Santana, Melquisedec Abiaré Dantas; Lima, Ruthnaldo Rodrigues Melo; Galvão-Coelho, Nicole Leite; Ladd, Fernando Vagner Lobo; Nascimento, Expedito Silva (Frontiers in Neuroanatomy, 2025)
IntroductionThe striatum (St) integrates cognitive, motor, and limbic functions and plays a critical role in processing emotions, motivation, and rewards. It may undergo several morphophysiological changes in neuropsychiatric diseases. Depression, a complex psychiatric disorder, affects millions of people around the world and leads to an increased risk of suicide, decreased quality of life, and functional impairment. Conventional treatments require prolonged use, leading to drug resistance; thus, new treatments and therapeutic strategies have been widely studied. Ayahuasca results from the joint infusion of the Banisteriopsis caapi vine and Psychotria viridis leaves have psychoactive properties, and its use in depression has shown promising results. Our objective was to morphoquantitatively evaluate the effects of ayahuasca on the St in an already validated model of juvenile depression induced in a non-human primate.MethodsSix marmosets were divided into three groups of two animals each. One group was kept in family life (FG), and two groups were socially isolated (IG). Isolation was carried out by separating the animal from all others in the colony. One of the isolated groups received doses of ayahuasca tea (AG) 3 days before and two times during the isolation period, while the other groups received the same dose of placebo. After 13 weeks of experimentation, euthanasia, and transcardiac perfusion were performed. The brains were sectioned and stained with thionin using the Nissl method. We employed stereological techniques to assess the striatum and investigate potential alterations in neuronal volume in socially isolated animals treated with ayahuasca. Equidistant sections of the caudate and putamen were analyzed for all measurements and selected by systematic and uniform sampling.Results and discussionStriatal neurons in the IG group exhibited significantly smaller volumes compared to those in the FG and AG groups. Our findings suggest that ayahuasca may prevent extensive neuronal volume loss, as observed in the IG, by acting as a prophylactic agent and buffering neural structural changes during chronical social isolation.